A Study of Relationship between Post Stroke Epilepsy and Solar Activity - Shagjaa, Tungalagtamir; Vilyamovich, Etremov Valery; Luvsannorov, Otgonbayar (Central Asian Journal of Medical Sciences, 2018)
Objective: Symptomatic seizure or post-stroke seizure are the most common seizure subtypes among the elderly. The purpose of our study was to better understand post-stroke epilepsy in relation to their cerebral location, and to find a possible link between epileptic seizure after stroke debut and the differences in solar activity. Methods: This retrospective chart review of patients who died from hemorrhagic stroke in Ulaanbaatar, Mongolia. Only patients with a hemorrhagic stroke from periods with relatively high solar activity (2000-2002 and 2013-2015) and relatively low solar activity (2008-2010) were considered. Results: Hemorrhagic stroke affected mainly patients between 45-59 years of age. Post-stroke epilepsy was less prevalent less during decreased solar activity years. Post-stroke epilepsy was more prevalent in patients with subarachnoid hemorrhage and brainstem hematoma and even more prevalent in patients with diabetes (p<0.01). Conclusion: Post-stroke epilepsy was less frequent during low solar activity years. Post-stroke epilepsy with concomitant brainstem hematoma resulted in poor outcomes following stroke.